2013
DOI: 10.4137/cgm.s11284
|View full text |Cite
|
Sign up to set email alerts
|

Animal Cancer Models of Skeletal Metastasis

Abstract: The bony skeleton is one of the most common sites of metastatic spread of cancer and is a significant source of morbidity in cancer patients, causing pain and pathologic fracture, impaired ambulatory ability, and poorer quality of life. Animal cancer models of skeletal metastases are essential for better understanding of the molecular pathways behind metastatic spread and local growth and invasion of bone, to enable analysis of host-tumor cell interactions, identify barriers to the metastatic process, and to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
(164 reference statements)
0
11
0
3
Order By: Relevance
“…Direct intraosseous injection of cancer cells eliminates problems of widespread metastasis, allowing studies to focus on the bone environment in metastasis. However, this experimental method introduces cancer cells into nonphysiological niches that may not be relevant to hematogenous spread of metastasis in breast cancer and other solid tumors ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Direct intraosseous injection of cancer cells eliminates problems of widespread metastasis, allowing studies to focus on the bone environment in metastasis. However, this experimental method introduces cancer cells into nonphysiological niches that may not be relevant to hematogenous spread of metastasis in breast cancer and other solid tumors ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In current models the clinical evaluation is done by observational findings or by semi-quantitative rating scales (BBB modified scale) after tumor engraftment, progression of paraparesis until paraplegia [30, 40, 41, 5658]. In our model we implemented a quantitative methodology to evaluate gait impairment in tumor implanted rats and demonstrated that stride length, velocity and time in the left hind limbs was affected; in some rats the right hind limb had a compensatory role by supporting more weight during locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques involved animal anaesthesia and surgery using an operating microscope, a dorsal skin incision, dissection of the paraspinal miscles For these reasons, immunodeficient mice are currently the commonest host animals used in in vivo cancer models. Indeed, in a recent review of animal models of skeletal metastasis, nude or severe combined immunodeficiency (SCID) mice were utilized in 75% of established models [32].…”
Section: Radiological and Histological Analysismentioning
confidence: 99%